Phenotypic Variations in External and Internal Fruit Quality Traits of Different Plum Accessions - Xia, Lehan; Chen, Long; Chen, Yuling; Huang, Zhenyu (Weon'ye gwahag gi'sulji, 2023)
Chinese plum (Prunus salicina Lindl.) is a fruit tree with a range of different fruit characteristics, such as different sizes, shapes, flavors, textures, and colors. The relationships between the economic characteristics, nutritional components, functional components, and antioxidant activities of plum fruit have rarely been reported. In order to select new and superior varieties of Chinese plum that are suitable for promotion in north China, eight Chinese plum varieties mainly cultivated in Henan Province (‘Purple amber plum’, ‘Green crisp plum’, ‘French plum’, ‘Princess plum’, ‘Huangganli’, ‘Huangjuli’, and ‘Friar plum’ from Zhengzhou city, and ‘Friar plum’ from Pingdingshan city) and five new breed accessions (‘7–15 plum’, ‘4–12 plum’, ‘1–24 plum’, ‘3–11 plum’, and ‘4–22 plum’) were used as subjects, with the main appearance indexes, nutrient components, functional components, and extract antioxidant activities from these fruits determined and analyzed. The results show that the same accessions of Chinese plum in different regions had the same fruit shape index values, whereas their fruit sizes, nutrient components, functional components and antioxidant activities showed significant differences. The total sugar content was extremely significantly positively correlated with reduced sugar contents and vitamin C (Vc) contents in the different accessions, with correlation coefficients of 0.926 and 0.708, respectively. The flavonoid contents and total phenolic contents in different accessions of plum fruits had an extremely significant positive correlation, with a correlation coefficient of 0.979 obtained. The flavonoid contents and total phenolic contents were significantly positively correlated with the ·OH scavenging capacity, showing correlation coefficients of 0.664 and 0.650, respectively. ‘Princess plum’ and ‘French plum’ had high flavonoid contents, total phenolic contents, and ·OH scavenging capacity levels; the ‘4–12 plum’ had a high triterpenoid acid content and DPPH· scavenging capacity; and ‘Huangganli’ had a high triterpenoid acid content and ·O2 －scavenging capacity. These results confirm that Chinese plums are a good source of natural phenolic antioxidants. KCI Citation Count: 0